The resuscitation status of implantable cardioverter-defibrillator patients according to electronic health records: are we ignoring the device?. (14th October 2021) - Aldous, R; Dayer, M; Furniss, G
Abstract: Introduction/Background: The Care Quality Commission (CQC) has recently raised concerns around resuscitation decisions in the UK. In our hospital an early resuscitation decision is made on admission, often by junior doctors, and documented in electronic notes. Concerns have been raised about the veracity of these discussions in patients with implantable cardioverter-defibrillators (ICD's). We investigated resuscitation status as documented on the electronic record for our ICD population. Methods: The ICD database was interrogated in 2020 for patients under current follow-up. Baseline demographics, hospital admissions over the past 5 years and ICD indications were documented from the electronic hospital records. All patients with an electronic do-not-resuscitate (DNR) flag on the electronic system were recorded, as were any documented resuscitation discussions and ICD deactivations between 2015 and 2020. Any patient deaths were recorded and correlated with resuscitation status and ICD status at the time of death. Results: Six-hundred and thirty-six patients with ICD's (transvenous, subcutaneous and CRT defibrillators) were identified under follow-up for the study period. The mean age of the population was 68 years old. 251 had an ischaemic cardiomyopathy, 209 had dilated cardiomyopathy, 50 prior ventricular fibrillation or tachycardia, 40 hypertrophic cardiomyopathy, 26 ARVC and the rest a channelopathy, congenital heart disease, sarcoidosis or valvular heart disease. Thirty-seven of the 636 patients were flagged on the electronic record as being not for resuscitation (5.9%). They had a mean age of 79 and 54% had an ischaemic cardiomyopathy. Of these, only 15 (39%) had their ICD deactivated and only 12 of those at the time of the resuscitation decision (32%). 15 of the 37 (39%) patients made DNR have subsequently died. Six of these (40%) had an active ICD at the time of death. In the 257 patients who had had a hospital admission in the study period, 34 were made not for resuscitation during the admission (13%) of whom 11 had their ICD deactivated at the time of discussion (32%). Patients with a DNR flag and an "active" ICD were contacted about deactivation of their ICD and offered discussion with a cardiologist or specialist nurse about ICD deactivation. Of these 9/27 (33%) stated that they wanted resuscitation and the alert was removed and the ICD kept on, although 3 subsequently had the device deactivated. Conclusions: In this study the majority of patients with ICD's who were made not for resuscitation on admission to hospital did not have their ICD therapies switched off, therefore putting them at risk of unnecessary ICD shocks. In addition, one third these patients subsequently chose to be for resuscitation after discussion. These complex decisions would be improved with the early involvement of cardiologists and specialist nurses. Funding Acknowledgement: Type of funding sources: None.